2020
DOI: 10.3390/jcm9030884
|View full text |Cite|
|
Sign up to set email alerts
|

Delayed Reconstruction of Palatomaxillary Defect Using Fibula Free Flap

Abstract: Introduction. The objective of this study was to evaluate a surgical technique and to present the results of delayed reconstruction of palatomaxillary defects using fibula free flap (FFF). Methods. A review was conducted for nine patients who underwent palatomaxillary reconstruction using FFF. Primary disease, type of reconstruction, defect area, fibula segment length and number of osteotomies, radiotherapy, and implant installation after FFF reconstruction were analyzed. Results. All nine patients underwent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The use of bone grafts on bony defects caused by tumors, trauma, or aging is an established and standardized procedure which has been clinically successful over a long period of time [ 1 , 2 , 3 ]. Many reports have been published on successful bone healing after autogenous, allogeneic, xenogeneic, and alloplastic bone grafting [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of bone grafts on bony defects caused by tumors, trauma, or aging is an established and standardized procedure which has been clinically successful over a long period of time [ 1 , 2 , 3 ]. Many reports have been published on successful bone healing after autogenous, allogeneic, xenogeneic, and alloplastic bone grafting [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…FFF can be harvested with an expendable long and rigid bone [15]. Byun et al reported nine cases of successful secondary palatomaxillary reconstructions using FFF, which indicates that the length of the vascular pedicle in FFF is su cient to reach the vessels on the contralateral side [16]. Thus, none of the four cases of secondary mandibular reconstructions performed at our institution required vein grafting, and all of them resulted in ap survival.…”
Section: Discussionmentioning
confidence: 80%
“…The fibula was first utilized by Hidalgo et al ( 64 ) for mandibular reconstruction in 1989. Compared with other options, the fibula has gained widespread use, owing to its versatility by offering great length and thickness of bone, intraosseous and segmental blood supply, and reliable skin paddle for simultaneous soft tissue reconstruction ( 65 , 66 ). Therefore, the use of the fibula for mandibular reconstruction is well accepted among numerous oral maxillofacial surgeons ( 62 ).…”
Section: Discussionmentioning
confidence: 99%